Children’s Bodily Expression and Learning Interaction Mediated by “Tabola Bale” - Indrahastuti, Tri; Martiara, Rina; Arifin, Syaiful (The Future of Education Journal, 2025)
This study aims to examine children’s bodily expression and learning engagement through the traditional song “Tabola Bale” as observed in TikTok and Instagram videos. Using a qualitative descriptive approach, the study employs video observation as the primary data source, supported by a literature review on embodied learning in elementary education. Publicly accessible videos featuring children’s responses to the song were selected purposively and analyzed thematically. The findings indicate that children display spontaneous bodily movements, rhythmic coordination, creative variations of movement, and positive affective expressions while engaging with the song. These bodily responses reflect active learning engagement that integrates motor, emotional, and social dimensions. The study also reveals that bodily expression serves as a medium of interaction, enabling meaningful participation through movement. The findings suggest that traditional songs hold pedagogical potential as embodied learning media in both classroom and digital learning contexts. This study contributes to elementary education by highlighting the relevance of culturally grounded songs in fostering active and meaningful learning experiences.